2009
DOI: 10.1016/j.polymer.2009.04.055
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of onion-like multilayered particles comprising mainly poly(iso-butyl methacrylate)-block-polystyrene by two-step AGET ATRP

Abstract: Synthesis of multilayered composite polymer particles comprising mainly poly(iso-butyl methacrylate)-block-polystyrene (PiBMA-b-PS) has been carried out by use of two-step activator generated by electron transfer for atom transfer radical polymerization (AGET ATRP) in aqueous microsuspension. PiBMA-Br macroinitiator seed particles were prepared in the first step, followed by swelling with styrene and subsequent second step (seeded) polymerization. The blocking efficiency in the second step was found to be cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…[94][95][96] In the initial study, the interior of near-symmetrical P i BuMA-b-PSt particles appeared onion-like, indicating phase separation into lamellar morphology, as expected based on volume fraction. 94 Results from the second study suggested an influence of blocking efficiency on phase separation.…”
Section: Atrpsupporting
confidence: 57%
See 1 more Smart Citation
“…[94][95][96] In the initial study, the interior of near-symmetrical P i BuMA-b-PSt particles appeared onion-like, indicating phase separation into lamellar morphology, as expected based on volume fraction. 94 Results from the second study suggested an influence of blocking efficiency on phase separation.…”
Section: Atrpsupporting
confidence: 57%
“…95 St polymerisation rate was significantly enhanced in miniemulsion conditions, but block copolymer Đ was high (2.4) due to a significant quantity of homo-P i BuMA and low blocking efficiency (<50%). By measuring the fraction of living chains at different stages of polymerisation (using a GPC dual detection method), it became evident that a significant quantity of dead chains formed during the early A rigorous study into a range of ligands and surfactants for AGET ATRP was performed by Xue et al for the synthesis of PSt-b-P n BuA-b-PSt using a difunctional ATRP initiator.…”
Section: 131mentioning
confidence: 97%
“…These results would provide an economical and facile method for the synthesis of fabricating fluorinated block copolymers. HFMA and IBMA were prepared according to the literature [31,34]. All other chemicals are used without further purification.…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to the initial concept, a single hydrophilic complex can also catalyze miniemulsion eATRP, if the cationic copper complex has strong interaction with an anionic surfactant. The catalyst/surfactant system produces ion pairs at the droplet surface to transport the catalyst into monomer droplets, thus enabling a controlled polymerization, enhanced by interfacial catalysis [82,83]. Different combinations of surfactant and hydrophilic Cu complexes were studied in the miniemulsion eATRP of n-butyl acrylate [38].…”
Section: Electrochemically Mediated Atom Transfer Radical Polymerizatmentioning
confidence: 99%